2013
DOI: 10.1103/physreve.88.043005
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcations and dynamics in convection with temperature-dependent viscosity in the presence of the O(2) symmetry

Abstract: We focus on the study of a convection problem in a two-dimensional setup in the presence of the O(2) symmetry. The viscosity in the fluid depends on the temperature as it changes its value abruptly in an interval around a temperature of transition. The influence of the viscosity law on the morphology of the plumes is examined for several parameter settings, and a variety of shapes ranging from spout-to mushroom-shaped are found. We explore the impact of the symmetry on the time evolution of this type of fluid,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…There also exist new critical thresholds at which stability is lost, thereby giving rise to new bifurcated structures. These stationary solutions are numerically obtained by using an iterative Newton-Raphson method as reported in [9,8].…”
Section: Stationary Solutions and Their Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…There also exist new critical thresholds at which stability is lost, thereby giving rise to new bifurcated structures. These stationary solutions are numerically obtained by using an iterative Newton-Raphson method as reported in [9,8].…”
Section: Stationary Solutions and Their Stabilitymentioning
confidence: 99%
“…The sign in the real part of the eigenvalue λ determines the stability of the solution: if it is negative, the perturbation decays and the stationary solution is stable, while if it is positive the perturbation grows over time and the stationary solution is unstable. For each unknown field expression, (5) is introduced into the system (1)-(3) and the equations are linearized inỹ, which are assumed to be small (see [9,8] for details). Together with their boundary conditions, the equations define a generalized eigenvalue problem.…”
Section: Stationary Solutions and Their Stabilitymentioning
confidence: 99%
“…The time dependent solutions displayed in Figure 7 although confirms the validity of the method do not particularly exhibit the influence of the symmetry, and thus the proposed spectral scheme does not show its power on this respect for the chosen test problem. However for other viscosity dependencies as the ones reported in [11] the current spectral method has successfully described solutions whose existence is related to the presence of the symmetry.…”
Section: Time Dependent and Transitory Regimesmentioning
confidence: 78%
“…The time dependent solutions found for the exponential viscosity law do not evidence the influence of the symmetry. However in [11] for different viscosity dependences, at high-moderate viscosity contrasts, it is reported that the proposed scheme is successful to this end. Finite element methods and finite volume methods have proven to be successful to reach extremely large viscosity contrasts up to 10 10 -10 20 and we have not improved these limits with spectral methods.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation